Política Nacional de Educação Especial: antecedentes, disputas, repercussões e análise sobre o Decreto 10.502/2020 - Caroline Carvalho da Costa Lima Landim (2022)
The present study is linked to the research line Policies, Institutional Practices and Social Exclusion/Inclusion of the Masters in Education at the Federal University in Mato Grosso do Sul, Pantanal Campus (UFMS/CPAN). The present research aims to analyze the process of elaboration of the normative and guiding documents of the National Policy on Special Education: Equitable, inclusive and with lifelong learning, as well as the manifestations about this in different social segments. The specific objectives consist of: Examining the positions, actions and mobilizations of actors and interest groups (researchers, family members, specialized private-assistance institutions, Federal Public Ministry, Ministry of Education, among others) in the process of elaborating the National Education Policy Special between 2016 and 2021, period of its discussion and attempts to change and to know the political guidelines of the normative and guiding documents that deal with the National Policy on Special Education: Equitable, Inclusive and Lifelong, enacted through Decree nº 10.502, of September 30, 2020. The research was developed through a qualitative approach and documentary research. For the analysis of the sources, objective of the research, the axes were organized: a) Lifelong Learning; b) Right to Inclusive Education; c) Specialized Educational Assistance; and d) Right to education, choice of the family in relation to educational institutions. The results point to the significance of the Lifelong Learning concept from its emergence in Brazilian legislation, which has been strained in the face of the repercussion of the theme, in addition to the intentions of the legislator, with open concepts, without specifying how and in what way it, will be materialized. In addition, the aforementioned Decree contravenes the constitutional charter, international treaties, legislation and other regulations in force, as it encourages the conservation of an alternative and parallel education system to the Target Audience of Special Education. The Decree also brings the misunderstanding about the difference between a classroom and the space occupied by the Specialized Educational Service, in addition to an expansion of service. The role of families is highlighted in several excerpts of the normative document, which emphasizes their participation and responsibility for the schooling process of their children, people already weakened in their experiences with their rights, in addition to presenting little or even the lack of adequate information. About the possibilities of care and development of their children. We saw that the principles of school inclusion guided educational documents, which has been a process marked by intense debates, especially Decree nº 10.502/2020, which creates a series of unconstitutional provisions, based on the segregation of people.